Perspectives of Experts in the Selection of Contents for a Course of Differential Equations in Engineering - José Luis Díaz Palencia (Multidisciplinary Journal for Education, Social and Technological Sciences)
This study investigates the teaching of Differential Equations in engineering education, focusing on expert opinions from diverse institutional backgrounds. The primary objectives were to understand expert perspectives on essential course content, justify their content choices, measure institutional gaps, and highlight the range of professional profiles. Through qualitative interviews with nine experts from academia and industry, we explored their views on the integration of Differential Equations in engineering curricula. The findings reveal a consensus on the importance of basic concepts to support physical models. Notably, experts highlighted variational calculus and energy representations as critical yet underrepresented areas in Differential Equations courses, essential for modeling complex, nonlinear problems. The study also states on the growing importance of computational methods and software in engineering education, advocating for an integrated approach aligning theoretical concepts with real-world applications. The expert opinions revealed a significant institutional influence on content perception, demonstrating a gap between traditional theoretical focus and modern, application-oriented approaches. The study suggests a need for curricular innovation in differential equations education, emphasizing practical applications and computational methods to bridge this gap between the two institutions considered in which the experts are adhered to.